2018
DOI: 10.1089/aivt.2018.0015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Liver Biology and the Tissue Response to Injury in Bioprinted Human Liver Tissues

Abstract: The rapid advancement of additive manufacturing technologies and their extension into biological systems have led to the emergence of a new category of cell-based models, namely bioprinted tissues. By combining automation and spatially controlled deposition of distinct components, such as cells, hydrogels, and mixtures thereof, the tissue engineer can now design and build tissues with far more control over the architecture of the end product. Bioprinted human liver tissues (BHLT) were one of the first commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This approach differs from several other biofabrication strategies in that the printed bioink is almost entirely cellular. The spatial arrangement of hepatocytes, stellate cells, and endothelial cells results in the formation of functional liver tissue units, which are used to study liver homeostasis and drug response . In a similar approach, bioprinted liver spheroids integrated into a liver‐on‐a‐chip platform demonstrated physiologic acetaminophen toxicity …”
Section: Applications Of Precision Biomaterialsmentioning
confidence: 99%
“…This approach differs from several other biofabrication strategies in that the printed bioink is almost entirely cellular. The spatial arrangement of hepatocytes, stellate cells, and endothelial cells results in the formation of functional liver tissue units, which are used to study liver homeostasis and drug response . In a similar approach, bioprinted liver spheroids integrated into a liver‐on‐a‐chip platform demonstrated physiologic acetaminophen toxicity …”
Section: Applications Of Precision Biomaterialsmentioning
confidence: 99%
“…32 The reduced throughput and the ability to miniaturize bioprinted tissue can be challenges, however, potentially limiting bioprinting's application to target validation or LO. 33 In addition, a NASH-like phenotype-including steatosis, ballooning hepatocytes, excessive collagen production, and inflammation-could be observed after exposing the 3D printed tissues to high levels of sugar and fatty acids, mimicking a diet regimen typically associated with obesity. 33,34 Comparisons of gene expression profiles between healthy and diseased human liver tissues and vehicle versus TGFβ-treated 3D bioprinted liver tissues showed a 5% overlap between human organs and 3D printed tissues.…”
Section: Civms Generated From 3d Bioprintingmentioning
confidence: 99%
“…33 In addition, a NASH-like phenotype-including steatosis, ballooning hepatocytes, excessive collagen production, and inflammation-could be observed after exposing the 3D printed tissues to high levels of sugar and fatty acids, mimicking a diet regimen typically associated with obesity. 33,34 Comparisons of gene expression profiles between healthy and diseased human liver tissues and vehicle versus TGFβ-treated 3D bioprinted liver tissues showed a 5% overlap between human organs and 3D printed tissues. 33 Subsequently, understanding the domain of validity for any cell model is critical to deciding how to apply the model for target validation and development of drugs to treat liver fibrosis.…”
Section: Civms Generated From 3d Bioprintingmentioning
confidence: 99%
“…Despite potential challenges, some studies have reported the successful determination of humanto-human differences. Emori et al 44) constructed and characterized 3D-cultures of fibroblast-like synoviocytes from rheumatoid arthritis (RA) patients and osteoarthritis (OA) patients. They showed that the 3D-RA and 3D-OA models differed in architecture and morphology.…”
Section: Future Challenges Related To Recon-stituted Human Organ Modelsmentioning
confidence: 99%